Clustering Pelanggan Menggunakan Algoritma K-Means Clustering di 7 MCC (Industry) Credit Card PT Bank CIMB Niaga, Tbk. - Pahrul Rojih; Jerry Heikal (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Electronics & gadgets, hotels, hospitals, groceries and F&B are the 5 biggest transaction usage at PT Bank CIMB Niaga, Tbk. which focuses on shopping activities using a credit card. The number of customer visits fluctuates so much that it is difficult to determine customer interest in buying a product. The purpose of this study is to identify the characteristics, product categories and merchants in the top 5 MCC (Industry) at PT Bank CIMB Niaga, Tbk. using the K-Means Clustering algorithm. There are three variables, namely customer characteristics, product categories, and merchants. Data processing is assisted by the SPSS V.25 application. Loyal Electronics & Gadgets customers are cluster 2. In addition, hotels also have loyal customers in cluster 6. Loyal Hospital customers are cluster 5. PT Bank CIMB Niaga, Tbk. (Card Business) is the 4th Book Bank in Indonesia which in the Usage Partnership Card Business Division focuses on shopping activities in various industries. The number of customer transactions is very fluctuating, making it difficult to determine customer interest in buying a product. The purpose of this research is to identify the characteristics, product categories and merchants in the top 5 transactions of CIMB Niaga credit card users in Indonesia using the K-Means Clustering algorithm. This article discusses how the grounded theory method is applied in a qualitative research. Qualitative research using the grounded theory method starts from data to achieve a theory and not starting from theory or to test a theory, so that in grounded theory research it is necessary to have various procedures or steps that are systematic and well planned. The qualitative research procedure using the grounded theory method consists of several stages, namely: a) the problem formulation stage, 2) the theoretical study application stage (if necessary), 3) the data collection and sampling stage, 4) the data analysis stage, and 5) the conclusion stage or report writing. However, the five stages of grounded theory research occur simultaneously. Researchers observe, collect and organize data and form theories from data at the same time. One of the important techniques in grounded theory research is the process of constant comparison in which each data is compared with all other data one by one. Data can be collected through interviews, observation, recording, or a combination of these methods. The quality of grounded theory research is largely determined by these steps which are carried out properly, correctly, and disciplined.